Motivating Students to Learn English by Responding to their Interests and Learning Styles - Moreno Aguilar Magda (Universidad Nacional de Colombia, 2001)
I observed that students from Barranquillita public school had a great lack of motivation, low interest in learning English and they did not like to interact in English class. They presumed that they could not learn a second language and it was not useful for them because they only wanted to finish school in order to go to work. In view of this, I considered it necessary to know my students´needs, likes, learning styles, preferences and dislikes better in order to design activities that would motivate their interest to learn English. Taking into account this issue, I decided to give my students the possibility to have contact and experience in the English language in order to increase their communicative competence.